2018
DOI: 10.18174/458502
|View full text |Cite
|
Sign up to set email alerts
|

Handboek melkveehouderij 2018/19

Abstract: Copyright en aansprakelijkheidNiets uit deze uitgave mag worden verveelvoudigd en/of openbaar worden gemaakt door middel van druk, fotokopie of op welke andere wijze dan ook, zonder voorafgaande schriftelijke toestemming van de uitgever. Auteurs en uitgever hebben de inhoud van deze uitgave met grote zorgvuldigheid en naar beste weten samengesteld naar de situatie zoals bekend medio 2010. Uitgever en redactie aanvaarden evenwel geen aansprakelijkheid voor schade, van welke aard dan ook, die het gevolg is van h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…The treatments 100%PL, 66%PL, 33%PL and 0%PL were allocated to twenty-four plots of 2.5 × 10.0 m according to a complete randomised block design, resulting in six replicates per treatment. Plantain seed was sown at 1.00, 0.66, 0.33 and 0.00 g m −2 for the treatments 100%PL, 66% PL, 33%PL and 0%PL, respectively, and ryegrass seed was sown at 3 g m −2 in all treatments (Remmelink et al 2018), following advised sowing rates for monocultures and mixtures and reported sowing rates for plantain monocultures by Minneé et al (2013) and Lee et al (2015). The same varieties and seedlines were used in the mesocosm and field experiment.…”
Section: Field Experimentsmentioning
confidence: 99%
“…The treatments 100%PL, 66%PL, 33%PL and 0%PL were allocated to twenty-four plots of 2.5 × 10.0 m according to a complete randomised block design, resulting in six replicates per treatment. Plantain seed was sown at 1.00, 0.66, 0.33 and 0.00 g m −2 for the treatments 100%PL, 66% PL, 33%PL and 0%PL, respectively, and ryegrass seed was sown at 3 g m −2 in all treatments (Remmelink et al 2018), following advised sowing rates for monocultures and mixtures and reported sowing rates for plantain monocultures by Minneé et al (2013) and Lee et al (2015). The same varieties and seedlines were used in the mesocosm and field experiment.…”
Section: Field Experimentsmentioning
confidence: 99%
“…At day 42, N was applied at a rate of 0, 6 or 12 g m −2 using a 50:50 mixture of liquid urea (CH₄N₂O) and ammonium nitrate (NH₄NO₃). The N fertilization level of 12 g m −2 was slightly higher compared to fertilization levels used for a May harvest in field conditions (about 10 g m −2 ) (Remmelink et al, 2018). A higher level was chosen because grass biomass growth and N uptake were expected to be higher in a greenhouse (Poorter et al, 2016).…”
Section: Pot Experimentsmentioning
confidence: 99%
“…On 2 September 2016, grasses were sown at a rate of 1327 germinating seeds m −2 , which was approximately equal to 3 g m −2 for diploids and 4.6 g m −2 for tetraploids. These are common sowing rates in practice for diploid and tetraploid grasses (Remmelink et al, 2018). The experiment was carried out until the first harvest in 2019.…”
Section: Field Experimentsmentioning
confidence: 99%
“…Omgekeerd wordt een disbalans in de microflora geassocieerd met ziekte. Het meest voor de hand liggend in dit opzicht is de ontwikkeling van (sub)klinische mastitis bij koeien en schapen na invasie en kolonisatie van de uier met specifieke pathogenen of micro-organismen uit de omgeving en het veroorzaken van symptomen zoals verhoogde somatische celtellingen, ontstekingsreacties in de uier en verminderde melkproductie en/of kwaliteit (Hillerton and Berry, 2005;Remmelink et al, 2014;Smith and Sherman, 2009). Recente studies tonen echter aan dat bij koeien met mastitis veranderingen in de melkmicroflora veel verder gaan dan die van de bekende oorzakelijke pathogenen.…”
Section: Microflora En Uiergezondheidunclassified